Cover Jurnal Media Teknik Sipil Vol. 13, No.2. Agustus 2015 - Cover . (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2015)
Cover Jurnal Media Teknik Sipil Vol. 13, No.2. Agustus 2015